Semen Quality and Freezability Analyses in the Ejaculates of Two Poitou Donkeys in the Southern Hemisphere - Ebel, Francisca; Ulloa, Omar; Strobel, Pablo; Ramírez-Reveco, Alfredo (Frontiers in Veterinary Science, 2021)
The Baudet du Poitou is a vanishing donkey breed recognized for engendering robust working mules. In Chile, only two pure breed Poitou males exist, which belong to the Chilean army and are used for mule production. We performed an extensive sperm and seminal analysis of these two jackasses aged 3 and 6 years and investigated the use of a simple hypometabolic extender for sperm cryopreservation. Computer-assisted sperm analysis showed high motility, velocity, and linearity in sperm movement. The seminal plasma analysis revealed that sodium and chloride were the main electrolytes, and globulins the main metabolites. Active and variable enzymatic activity was observed. New information is reported about gamma-glutamyltransferase, aspartate aminotransferase, zinc, and magnesium concentrations in seminal plasma of Poitou donkeys. Ejaculates among jackasses showed some variability due to individual variability and different stages in sexual maturation according to age. The cryopreservation analysis indicated that a simple hypometabolic extender preserved the integrity of sperm membranes similarly to the control extender (p > 0.05), although with a notable decline in post-thawed motility indicators (p < 0.05). The post-thawed membrane preservation could be used for sperm cryopreservation and advanced technologies such as ICSI. We report new information on Poitou donkey semen and cryopreservation in the Southern Hemisphere that could be useful in donkey breeding and conservation programs to develop strategies that improve the effectiveness of population management of this breed.